Еpidemiological aspects of ixodid tick-borne borrelioses in Kemerovo region - О. M. Drozdova; A. R. Efimova; Т. Е. Bondarenko; М. A. Shmakova (Фундаментальная и клиническая медицина)
Aim. To study the epidemiological patterns of Lyme disease in the Kemerovo Region. Materials and Methods. We performed a descriptive and retrospective epidemiological study of 3,133 cases to investigate the spread of Lyme disease in the Kemerovo Region during the recent 15 years (2005-2019). 1,000 ticks of the Ixodes genus were investigated for the presence of Borrelia burgdorferi senso lato s. l. and Borrelia miyamotoi DNA, while 98 patients with tick-borne fevers of unknown aetiology were examined to identify the DNA of the causative agents of ixodid tick-borne borrelioses and tick-borne recurrent fevers by PCR. Antibodies to Borrelia in the patient serum were detected by enzyme-linked immunosorbent assay. Results. In the structure of tick-borne infections over the study period, the proportion of ixodid tickborne borrelioses was 29.88% [95% CI = 27,25- 32,61]. The incidence demonstrated a 2,8-fold increase from 3.2200 / 0000 [95% CI = 3,20-4,57] in 2005 up to 9,2000 / 0000 [95% CI = 12,47-15,31] in 2019. Annually, around 30,000 people suffered from the tick attack. Bite rates ranged from 813.510 / 0000 [95% CI = 804,05-825,50] to 1506.100 / 0000 [95% CI = 1491,57-1520,02]. Two-thirds of the victims were attacked by ticks during the unorganized recreation in the forest, gathering wild plants and working in the garden plots. Lyme disease was characterised by a spring-summer seasonality with a maximum incidence in June. Rural population showed a higher level of ixodid tick-borne borrelioses incidence as compared to the urban population. In age groups, the maximum rates were recorded in the individuals over 40 years of age. Northern territories of the region showed the highest prevalence of ixodid tickborne borrelioses. In a study of 1000 ticks, DNA of Burgdorferi s. l. and B. miyamotoi was detected in 32.5% and 5.2%, respectively. In contrast, B. miyamotoi prevailed in patients with tick-borne fevers (13.26% of positive cases in comparison with 4.08% for B. Burgdorferi s. l. Tick-borne aetiology of the diseases was confirmed by the enzyme-linked immunosorbent assay measurements. Conclusions. Ixodid tick-borne borrelioses is prevalent in Kemerovo Region, demonstrating an upward and seasonal trend. Risk groups include rural population and those > 40 years of age. A high level of Ixodes persulcatus-mediated transmission of B. burgdorferi s. l. and B. miyamotoi infections was revealed; the latter agent often caused tick-borne fevers of unknown etiology